USABILITY STUDY ON THE INTERFACE OF AN ARTIFICIAL INTELIGENCE SYSTEM FOR CREATIVITY SUPPORT (Human Factors in Design, 2018)
Organizations should enhance its creativity skills, the basis to fulfill the changing customers’ needs. Creativity techniques are powerful allies in the innovation process for building adequate ideas. Each technique has appropriate use situations, and selecting them requires experience from a facilitator. As a rare asset, human expertise can be represented using Artificial Intelligence approaches. The developed prototype identifies the design team’s scenario through questions, correlating adequate creativity techniques. To develop a clearer and more intuitive system, we investigate interface and usability aspects through questionnaires with students and design specialists.